Pengembangan Modul Discon Sains Di Sekolah Dasar - Azizah Azizah; Puji Winarti (Prodi PGSD FIP UNM, 2018)
This study is aimed at (1) describing the characteristics of the Discon module in the learning of the Science Practicum in Class IV elementary school; (2) knowing the validity, practicality, and effectiveness of the Discon Science module in Class IV elementary school. This research is a type of research and development. This study aims to develop educational products in the form of modules that can be used in science learning. The research model used was adopted from Gravemeijer & Cobb's three-phase R & D model, namely the initial research phase, development phase and assessment phase. The effectiveness test of the module was analyzed using n-gain. The results of the study show that the module validity value is 50.5 with valid criteria. Practicality test of the module which yields 63.8 with very practical criteria. The effectiveness test using n-gain obtained a value of 0.71 in the high category. From the results of the study it can be concluded that the Discon Science Module in the Class IV primary school developed has fulfilled the criteria of validity, practicality, and effectiveness so that it can be used as one of the teaching materials in science learning in primary schools.